A Potential Therapeutic Target RNA-binding Protein, Arid5a for the Treatment of Inflammatory Disease Associated with Aberrant Cytokine Expression - Masuda, Kazuya; Kishimoto, Tadamitsu (Current Pharmaceutical Design, 2018)
Background: Infection, tissue damage and aging can cause inflammation with high levels of inflammatory cytokines. Overproduction of inflammatory cytokines often leads to systemic inflammatory response syndrome (SIRS), severe sepsis, and septic shock. However, prominent therapeutic targets have not been found, although the incidence of sepsis is likely to increase annually. Our recent studies indicate that some RNA-binding proteins, which control gene expression of inflammatory cytokines at the post-transcriptional level, may play a critical role in inflammatory diseases such as sepsis. Results: 1) One of the RNA-binding proteins, AT-rich interactive domain-containing 5a (Arid5a) promotes cytokine production through control of mRNA half-lives of pro-inflammatory molecules such as IL-6, STAT3, T-bet, and OX40 in activated macrophages and T cells. Arid5a KO mice are refractory to endotoxin shock, bleomycininduced lung injury, and inflammatory autoimmune disease. 2) Chlorpromazine (CPZ), which is recognized as a psychotic drug, impairs post-transcriptional gene expression of Il6 in LPS-stimulated macrophages: CPZ inhibits the binding activity of Arid5a to the 3'UTR of Il6 mRNA, thereby destabilizing Il6 mRNA possibly through suppression of Arid5a expression. 3) CPZ has strong suppressive effects on cytokine production such as TNF-α in vivo. Mice with treatment of CPZ are resistant to lipopolysaccharide (LPS)-induced shock. Conclusion: Thus, Arid5a contributes to the activation of macrophages and T cells through positive control of mRNA half-lives of inflammatory cytokines and its related molecules, which might lead to cytokine storm. Interestingly, Arid5a was identified from an inhibitory effect of CPZ on IL-6 production in macrophages activated by LPS. Therefore, CPZ derivatives or Arid5a inhibitors may have a potential to suppress severe sepsis through control of post-transcriptional gene expression.
Keywords: inflammation